2015
DOI: 10.1016/j.socscimed.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Black lives matter: Differential mortality and the racial composition of the U.S. electorate, 1970–2004

Abstract: Excess mortality in marginalized populations could be both a cause and an effect of political processes. We estimate the impact of mortality differentials between blacks and whites from 1970 to 2004 on the racial composition of the electorate in the US general election of 2004 and in close statewide elections during the study period. We analyze 73 million US deaths from the Multiple Cause of Death files to calculate: (1) Total excess deaths among blacks between 1970 and 2004, (2) total hypothetical survivors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 50 publications
3
84
0
Order By: Relevance
“…The association between health status and voting patterns in previous US election cycle has been examined previously. A recent study found that excess mortality among blacks may have led to outcomes of state-level elections that would not have been observed if blacks had similar mortality to whites (Rodriguez et al, 2015). Analysis of the results of the Republican Party primaries conducted in early 2016 highlighted that support for Donald Trump was higher in areas with increased mortality in middle aged nonHispanic whites (Guo, 2016).…”
Section: Patient Involvementmentioning
confidence: 99%
“…The association between health status and voting patterns in previous US election cycle has been examined previously. A recent study found that excess mortality among blacks may have led to outcomes of state-level elections that would not have been observed if blacks had similar mortality to whites (Rodriguez et al, 2015). Analysis of the results of the Republican Party primaries conducted in early 2016 highlighted that support for Donald Trump was higher in areas with increased mortality in middle aged nonHispanic whites (Guo, 2016).…”
Section: Patient Involvementmentioning
confidence: 99%
“…Differential mortality by race may also serve in some ways to perpetuate health disparities and contribute to the stubborn persistence of the problem (Rodriguez et al, 2015). The relative lack of minority individuals who survive into old age and the relative robustness of this group due to selective survival mechanisms might also explain other findings, such as why African Americans are less likely to use nursing homes and other sources of more formal support in old age (Markides & Machalek, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This excess mortality of African Americans is believed to be an important indicator of persistent health disparities (Williams, 2012), and its impact on the population could have far-reaching consequences including socioeconomic and political effects that might serve to perpetuate those disparities (Rodriguez et al, 2015) and a lack of sufficient aging-related services being developed for African American and other disadvantaged populations (Markides & Machalek, 1984). For all of these reasons, it is vital that we better understand the root causes of this excess mortality experienced by African Americans in comparison to Whites and design programs and policies that seek to reduce this important disparity.…”
Section: Introductionmentioning
confidence: 99%
“…15 Systematic restrictions on voting which disproportionally and negatively impact racial and ethnic minorities and the poor may promote health disparities by excluding substantial portions of the population from participating in the political process. 2, 10, 15, 19 Over 6 million Americans are prohibited from voting due to felony disenfranchisement laws restricting voting rights for individuals convicted of felony offenses. 20, 21 The length of voting prohibitions vary by state, with the period of disenfranchisement for persons convicted of a felony offense ranging from the duration of the sentence to lifetime prohibition.…”
Section: Introductionmentioning
confidence: 99%
“…20, 21 The potential impact of felony disenfranchisement varies substantially across states and racial and ethnic groups. 2, 10, 19, 21, 22 One in every 13 African American adults is disenfranchised, as compared to 1 in 56 non-African American adults. 21 The South has some of the strictest (e.g., lifetime prohibition) and highest rates of felony disenfranchisement, with as many as 1 in 4 African Americans in some states prohibited from voting.…”
Section: Introductionmentioning
confidence: 99%